Application of Integrated Hardware and Software System "PRIZNAK-10M" for Measuring Power-Frequency Electric and Magnetic Fields in Electric Networks - Kurbatsky, Victor (Electrical, Control and Communication Engineering, 2010)
One of the urgent problems in modern power industry is to provide safety of man staying in the affected area of electric and magnetic fields generated by operating electric facilities. The paper presents integrated hardware and software system "PRIZNAK-10M", intended for measurement of power-frequency electric and magnetic fields in electric networks. Integrated hardware and software system put into practice the methods of measurements, met the regulatory documents effected in electric networks of Russia. The recommendations have been developed to provide the man safely at the facilities studied.